Valuing Environmental Amenities Using Stated Choice Studies A Common Sense Approach to Theory and Practice - Kanninen, Barbara J.; Kanninen, Barbara J. (The Economics of Non-Market Goods and Resources,, 2007)
This book provides practical, research-based advice on how to conduct high-quality stated choice studies. It covers every aspect of the topic, from planning and writing the survey, to analyzing results, to evaluating quality. Chapters by highly-regarded academics and professionals are provided on rarely-discussed topics such as "supporting questions” and experimental design, as well as state-of-the-art multinomial choice modelling, attribute processing, the role of information, and lessons learned from the field of experimental economics. There is no other book on the market today that so thoroughly addresses the methodology of stated choice. Academics and practitioners in fields such as environmental, health and transportation economics, and marketing, will need this book on their shelves – and they will refer to it often.